2020
DOI: 10.3390/en13153837
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Persistent and Transient Energy Efficiency in Belt and Road Countries: A Stochastic Frontier Analysis

Abstract: In this paper, we examine the energy efficiency performance of the Belt and Road Initiative (BRI) countries using a newly developed panel data stochastic frontier model that allows for estimation of both persistent and transient efficiency while controlling for random country effects and noise. By this, we contribute to the energy economic literature by providing a complete picture of the level of persistent, transient, and total energy efficiency estimates from a cross country perspective for a panel of 48 BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 66 publications
5
19
0
Order By: Relevance
“…The coefficients of the variable BRI•Post were significantly positive at the 10% and 5% levels, as shown in columns (1) and (2), respectively. It shows that the policy of BRI has a significantly increasing effect on the energy efficiency of BRI countries, which is consistent with our assumption in Section 3.1 and previously related literature (e.g., [26][27][28][29][30][31][32][33][34][35][36]. Actually, according to the energy efficiency data of BRI countries available in this paper, the average energy efficiency of the BRI countries has risen from 8.62 in the year 2012 to 9.04 in the year 2018.…”
Section: The Impact Of Bri On Energy Efficiencysupporting
confidence: 91%
See 1 more Smart Citation
“…The coefficients of the variable BRI•Post were significantly positive at the 10% and 5% levels, as shown in columns (1) and (2), respectively. It shows that the policy of BRI has a significantly increasing effect on the energy efficiency of BRI countries, which is consistent with our assumption in Section 3.1 and previously related literature (e.g., [26][27][28][29][30][31][32][33][34][35][36]. Actually, according to the energy efficiency data of BRI countries available in this paper, the average energy efficiency of the BRI countries has risen from 8.62 in the year 2012 to 9.04 in the year 2018.…”
Section: The Impact Of Bri On Energy Efficiencysupporting
confidence: 91%
“…(1) Positive impacts According to Han et al [4], the BRI can enhance energy efficiency convergence among BRI nations via regional cooperation and energy trade with China. Based on the panel data of 48 BRI countries for the period of 1990-2015, Sun et al [26] also reached a similar conclusion. They also found that high-income BRI countries perform better than the lower-income BRI countries.…”
Section: Literature Reviewmentioning
confidence: 65%
“…motorcycles). This supports the results of Filippini and Zhang (2016); Adom et al (2018); Sun et al (2020a). Urbanization also has a significant negative effect on energy demand in model ( 2)-( 4), which endorses the findings of Keho (2016) and Adom et al (2018).…”
Section: Estimated Energy Demand Modelsupporting
confidence: 88%
“…However, in all three models, the estimated income elasticity is positive and significant. The positive effect of income demonstrates that increased incomes in developing economies have a larger scale effect than technical effects, which is similar to results of Adom et al (2018); Sineviciene et al (2017); Filippini and Zhang (2016); Sun et al (2020a).…”
Section: Estimated Energy Demand Modelsupporting
confidence: 77%
“…The "One belt, one road" plan has created favorable conditions for the sustainable development of Northwest China [3] . The northwest of China has been a key poverty alleviation area for a long time because of its vast territory, sparse population and rich resources.…”
Section: Calculation Of Economic and Trade Influence Degree Of Centramentioning
confidence: 99%